Environmental enrichment increases hippocampal glucocorticoid receptors and decreases GluA2 and protein kinase M zeta (PKMz) trafficking during chronic stress: A protective mechanism? - Zanca, Roseanna M.; Braren, Stephen; Maloney, Brigid; Schrott, Lisa; Luine, Victoria; Serrano, Peter (Frontiers in Behavioral Neuroscience, 2015)
Environmental enrichment (EE) housing paradigms have long been shown beneficial for brain function involving neural growth and activity, learning and memory capacity, and for developing stress resiliency. The expression of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit GluA2, which is important for synaptic plasticity and memory, is increased with corticosterone (CORT), undermining synaptic plasticity and memory. Thus, we determined the effect of EE and stress on modulating GluA2 expression in Sprague-Dawley male rats. Several markers were evaluated which include: plasma CORT, the glucocorticoid receptor (GR), GluA2, and the atypical protein kinase M zeta (PKMz). For one week standard- (ST) or EE-housed animals were treated with one of the following four conditions: (1) no stress; (2) acute stress (forced swim test [FST] on day 7); (3) chronic restraint stress (6 h/day for 7 days); (4) chronic + acute stress (restraint stress 6 h/day for 7 days + FST on day 7). Hippocampi were collected on day 7. Our results show that EE animals had reduced time immobile on the FST across all conditions. After chronic + acute stress EE animals showed increased GR levels with no change in synaptic GluA2/PKMz. ST-housed animals showed the reverse pattern with decreased GR levels and a significant increase in synaptic GluA2/PKM. These results suggest that EE produces an adaptive response to chronic stress allowing for increased GR levels, which lowers neuronal excitability reducing GluA2/PKMz trafficking. We discuss this EE adaptive response to stress as a potential underlying mechanism that is protective for retaining synaptic plasticity and memory function.